Interfacial properties of diffusion bonded Ti-6Al-4V to AISI 304 stainless steel by inserting a Cu interlayer - Ozdemir, N.; Bilgin, B. (Springer London Ltd, 2009)
The joining characteristics of Ti-6Al-4V with AISI 304 stainless steel by inserting a Cu interlayer was investigated in a vacuum-free diffusion bonding process. The diffusion bonds were carried out in the temperature range of 820, 850 and 870A degrees C for 50, 70 and 90 minutes, respectively, under 1 MPa load in argon atmosphere. The joining performances of diffusion bonded Ti-6Al-4V to AISI 304 were studied experimentally. The influence of the insert layer on the microstructure-formed interface region, bonding quality and mechanical properties have also been estimated. The microstructures formed in the diffusion region were observed and determined by scanning electron microscopy (SEM). The microhardness across and perpendicular to the interface were measured and the strength of the joints were also determined with lap-shear test.
Keywords: Ti-6Al-4V titanium alloy; AISI 304 stainless steel; Diffusion bonding; Cu interlayer